CONSTRUCTION OF THE ACCOUNTING THEORY FROM CASE ANALYSIS - Choy Zevallos, Elsa Esther (2016)
For some authors accounting is considered as a social practice whose scope is the economic context with impact on organizations. The case study is a methodology that can link theory with practice and generate a source of knowledge to construct theories and an accounting doctrine.Accounting is applied with greater intensity in management: business, governmental, environmental, financial, among others; they all have experienced significant casuistry that deserve to be disseminated among students and / or accounting professionals and related sciences.The purpose is to relate accounting research with professional practice. The lack of linking theory with the daily happenings of the organizations in general and accounting practice in particular, makes the theorization about accounting without paying attention to empirical research, which is sometimes criticized and questioned, but it is important as part of the process of knowledge. In this scenario, the question arises: How do we demand accounting theory evolution when relevant facts are not collected from the practice in order to be investigated?The study is descriptive and provides some applicative results to the accounting science, knowledge transfer and confirmation of accounting theories.